Differentiating Knowledge of Agave Landraces, Uses, and Management in Nanacamilpa, Tlaxcala. Issue Volume 42:Issues 1(2022) (March 2022) - Trejo, Laura; de Lourdes Luz Velázquez, María; Vallejo, Mariana; Montoya, Adriana
Pulque is a product made from the fermentation of the sap (aguamiel ) of certain agaves and its consumption has been recorded since pre-Hispanic times. The effort to recognize the landraces of the Agave genus used to produce pulque and the study of its traditional knowledge remain limited. Studies regarding this topic have centered on farmers (experts) with the biggest production capacity. This work analyzes in different ways the knowledge that experts and non-experts (general population) have regarding the usage and management of agave landraces in Nanacamilpa, Tlaxcala, one of the most iconic pulque production locations in Mexico. Two-hundred and twenty-two semi-structured interviews were carried out with non-experts and 22 with experts. The non-experts recognized 12 agave landraces, whilst experts recognized eight landraces that are mainly used to obtain aguamiel. The most important landrace that they identified was the Agave salmiana, due to the sweetness of its aguamiel and flexibility of its leaves. In total, 92 uses of agave landraces were recorded: 64 direct uses and 28 derivative uses. The oldest participants know most of its uses, but the younger participants recorded 48 uses, which indicates that agaves are a valuable resource for new generations. Experts mentioned uses directly related to the production of plants, aguamiel, and pulque, whilst non-experts included more categories of use. The agaves used for the production of pulque are of great importance for local biodiversity, culture, and economy.